A History of Industrial Hygiene: the Clinica del Lavoro in Milan and the Italian Association of Industrial Hygienists - Cavallo, Domenico Maria; Cattaneo, Andrea; Spinazzè, Andrea (La Medicina del Lavoro, 2019)
In 1969, the Italian Association of Industrial Hygienists (AIDII) was founded in Milan by Academics working at the Clinica del Lavoro, one of the oldest institutions for work prevention in the world and within the most prolific institutes in the world on Occupational Medicine and Industrial Hygiene. AIDII was founded as a scientific association with the primary purpose of promoting the development, deepening and dissemination of Industrial Hygiene, the scientific discipline aimed at identifying, assessing and controlling chemical, physical and biological risk factors (as well as transversal risks) either inside or outside the workplace, which can alter the health and well-being status of workers and/or the general population, for the purpose of effective prevention and protection of human health. Over the decades, the activities of AIDII have evolved to meet some of the current needs and challenges, while remaining consistent with the basics set by the founders.